Immune repertoire sequencing reveals differences in treatment response to camrelizumab plus platinum-based chemotherapy in advanced ESCC - Zhang, Xiaoling; Zhao, Wenqi; Du, Yunyi; Su, Fei; Zhang, Yuexiang; Wang, Hui; Li, Yongai; Liu, Min; Gao, Yangjun; Cai, Linlin; Feng, Tingting; Wang, Mei; et al. (Frontiers in Immunology, 2025)
This study evaluated the efficacy and safety of camrelizumab combined with platinum-based chemotherapy (taxanes [T] or fluorouracil agents [F] plus platinum [P] drugs) as the first-line treatment in advanced esophageal squamous cell carcinoma (ESCC), using immune repertoire sequencing (IRS) to explore treatment response mechanism. In this multi-center, prospective cohort study, 88 patients received camrelizumab plus TP or FP, achieving a 1-year progression-free survival of 56.8% and overall survival of 68.2%. The objective response rate (ORR) was 64.8%, with a disease control rate of 91.1%. While most treatment-related adverse events were mild, 12.5% of patients experienced grade ≥3 toxicities. IRS showed significant differences in T-cell receptor (TCR) β-chain and immunoglobulin heavy chain between patients with (ORR group) or without ORR (non-ORR group), particularly in the distribution and expression of some genes. Specifically, we found the significant differences in the amino acid composition of complementarity determining region 3 (CDR3) polypeptide sequences in TCR and B-cell receptor (BCR) between the ORR and non-ORR groups. For TCR, we observed substantial oligoclonal enrichment and differences in the abundance of specific V and J genes. Similarly, for BCR, we detected differences in the clonotype abundance of CDR3 polypeptide segments and identified several differential V genes. Camrelizumab combined with platinum-based chemotherapy is effective and well-tolerated as the first-line treatment for ESCC, and IRS may reveal mechanism influencing treatment response.